City of God [videorecording (Blu-Ray)] - Nachtergaele, Matheus, 1969-; Rodrigues, Alexandre, 1983-; Lins, Paulo, 1958- (Miramax award-winning collection., 2014)
See the world's most notorious slum, Rio de Janeiro's City of God, where combat photographers and police rarely go. Based on the true story of a young man who grew up on these streets and whose ambition as a photographer is our window in and his only way out.